An Assessment of Inappropriate Antibiotic Use and Guideline Adherence for Uncomplicated Urinary Tract Infections. (10th August 2018) - Durkin, Michael J; Keller, Matthew; Butler, Anne M; Kwon, Jennie H; Dubberke, Erik R; Miller, Aaron C; Polgreen, Phillip M; Olsen, Margaret A
Abstract: Background: In 2011, The Infectious Diseases Society of America released a clinical practice guideline (CPG) that recommended short-course antibiotic therapy and avoidance of fluoroquinolones for uncomplicated urinary tract infections (UTIs). Recommendations from this CPG were rapidly disseminated to clinicians via review articles, UpToDate, and the Centers for Disease Control and Prevention website; however, it is unclear if this CPG had an impact on national antibiotic prescribing practices. Methods: We performed a retrospective cohort study of outpatient and emergency department visits within a commercial insurance database between January 1, 2009, and December 31, 2013. We included nonpregnant women aged 18–44 years who had an International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis code for a UTI with a concurrent antibiotic prescription. We performed interrupted time series analyses to determine the impact of the CPG on the appropriateness of the antibiotic agent and duration. Results: We identified 654 432 women diagnosed with UTI. The patient population was young (mean age, 31 years) and had few comorbidities. Fluoroquinolones, nonfirstline agents, were the most commonly prescribed antibiotic class both before and after release of the guidelines (45% vs 42%). Wide variation was observed in the duration of treatment, with >75% of prescriptions written for nonrecommended treatment durations. The CPG had minimal impact on antibiotic prescribing behavior by providers. Conclusions: Inappropriate antibiotic prescribing is common for the treatment of UTIs. The CPG was not associated with a clinically meaningful change in national antibiotic prescribing practices for UTIs. Further interventions are necessary to improve outpatient antibiotic prescribing for UTIs.